Argentina report on deforestation 2000-2024 - Jorge, Nicolas (International Food Policy Research Institute, 2025)
Argentina’s native forests are essential components of the country’s ecological and economic fabric. These ecosystems provide a wide array of services, from biodiversity conservation and water regulation to carbon storage and support for local livelihoods. However, human activity and natural events such as wildfires resulted in ongoing forest loss, particularly in regions like Gran Chaco. Understanding the dynamics of forest loss over time is crucial for evaluating the effectiveness of conservation policies and for guiding future land-use decisions.